A clustered origin for isolated massive stars. Issue 3 (23rd November 2017) - Lucas, William E; Rybak, Matus; Bonnell, Ian A; Gieles, Mark
Abstract: High-mass stars are commonly found in stellar clusters promoting the idea that their formation occurs due to the physical processes linked with a young stellar cluster. It has recently been reported that isolated high-mass stars are present in the Large Magellanic Cloud. Due to their low velocities, it has been argued that these are high-mass stars which formed without a surrounding stellar cluster. In this paper, we present an alternative explanation for the origin of these stars in which they formed in a cluster environment but are subsequently dispersed into the field as their natal cluster is tidally disrupted in a merger with a higher mass cluster. They escape the merged cluster with relatively low velocities typical of the cluster interaction and thus of the larger scale velocity dispersion, similarly to the observed stars. N -body simulations of cluster mergers predict a sizeable population of low-velocity (≤20 km s −1 ), high-mass stars at distances of >20 pc from the cluster. High-mass clusters in which gas poor mergers are frequent would be expected to commonly have haloes of young stars, including high-mass stars, which were actually formed in a cluster environment.